From unfractionated heparin to pentasaccharide: Paradigm of rigorous science growing in the understanding of the in vivo thrombin generation. (January 2020) - Spadarella, Gaia; Di Minno, Alessandro; Donati, Maria Benedetta; Mormile, Mauro; Ventre, Itala; Di Minno, Giovanni
Abstract: Following a chance discovery made by a medical student who was searching for a clot-promoting activity in tissue extracts, it took 15–20 years to attain the therapeutic use of standard unfractionated heparin (UFH), due to problems with the purification and extraction of the active material. Soon it was found that: 1) thrombin inactivation by UFH was associated with the formation of molecular complexes between antithrombin and the activated forms of factor X (FXa) and thrombin, 2) low-molecular-weight fractions of UFH lose their antithrombin activity while still interacting with FXa, 3) a pentasaccharide sequence of UHF increases FXa (but not thrombin) inactivation by antithrombin. Low-molecular-weight heparins (LMWHs) with little effect on thrombin and strongly active versus FXa were then developed. In patients, LMWHs (and the pentasaccharide sequence) came up as a useful class of drugs to prevent and treat thrombosis, their greatest advantage over UFH being the convenience of the once/twice daily subcutaneous injections at a fixed dose without any laboratory monitoring. In addition to providing major information on in vivo modulation of thrombin generation, the heparin saga served as a paradigm to support an alternative coagulation scheme that includes platelets and tissue factor as integral parts of the model. Forthcoming work with this scheme – also supported by studies in hemophilia and rare bleeding disorders – is expected to provide major hints for understanding why some patients benefit more than others from the small amount of thrombin they form and directions to tailor prevention and treatment of thromboembolic disorders.